An Extracellular Redox Signal Triggers Calcium Release and Impacts the Asexual Development of Toxoplasma gondii - Alves, Eduardo; Benns, Henry J.; Magnus, Lilian; Dominicus, Caia; Dobai, Tamás; Blight, Joshua; Wincott, Ceire J.; Child, Matthew A. (Frontiers in Cellular and Infection Microbiology, 2021)
The ability of an organism to sense and respond to environmental redox fluctuations relies on a signaling network that is incompletely understood in the apicomplexan parasite Toxoplasma gondii. The impact of changes in redox upon the development of this intracellular parasite is not known. Here, we provide a revised collection of 49 genes containing domains related to canonical antioxidant groups, with their encoded proteins widely dispersed throughout different cellular compartments. We demonstrate that addition of exogenous H2O2 to human fibroblasts infected with T. gondii triggers a Ca2+ flux in the cytosol of intracellular parasites that can induce egress. In line with existing models, egress triggered by exogenous H2O2 is reliant upon both Calcium-Dependent Protein Kinase 3 and diacylglycerol kinases. Finally, we show that the overexpression of the active catalytic domain of glutaredoxin in the parasitophorous vacuole severely impacts parasite replication. These data shed light on the rich redox network that exists in T. gondii, evidencing a link between extracellular redox and intracellular Ca2+ signaling that can culminate in parasite egress. Our findings also indicate that the redox potential of the intracellular environment contributes to normal parasite growth. Combined, our findings highlight the important role of redox as an unexplored regulator of parasite biology.